"Changing the channel": Hybrid masculinity in a men's prison. Issue 2 (11th September 2020) - Umamaheswar, Janani
Penological literature has focused extensively, and often exclusively, on the "hypermasculine" nature of men's prisons. A separate and relatively recent body of sociological research has explored "hybrid masculinities, " whereby (usually privileged) men selectively enact traits conventionally associated with subordinate masculinities and even femininities. In this article, I draw on 24 in-depth interviews with incarcerated men to argue that these men construct hybrid masculinities in response to their feelings of insecurity and to resist the hypermasculine prison environment. In so doing, I link theoretical literature on hybrid masculinities with penological research to explore how a particularly marginalized group of men construct hybrid masculinities to cope with and challenge hegemonic masculinity in prison.